Drought, herbivory and combined stress caused treatment-specific changes in phytohormones, but species-specific changes in secondary metabolite profiles in thyme - Alipour, Maryam; Martinelli, Laure; Groten, Karin; Mithöfer, Axel (Frontiers in Plant Science, 2025)
Thyme species are important medicinal herbs predominantly cultivated in arid regions. They increasingly experience the adverse effects of climate change, particularly drought. Although abiotic stress effects on thyme have been examined, limited information exists on insect herbivory or combined stress response. This study investigated the effects of drought stress, herbivory and their combination on secondary metabolism, phytohormone regulation and insect performance in three thyme species: Thymus serpyllum (drought-sensitive), T. kotschyanus (drought-tolerant), and T. vulgaris. Plants were exposed for three weeks to four treatments: control, drought (40% field capacity), Spodoptera littoralis larvae herbivory, and combined drought × herbivory. Herbivore performance was documented. Levels of volatile terpenes, phenolic compounds, and phytohormones were analyzed using GC-MS and LC-MS/MS. Gene expression of terpenoid biosynthesis enzymes (TPS2, CYP71D178, CYP71D181) was quantified via RT-qPCR. Results revealed species-specific responses in secondary metabolism and measured gene expression, with herbivory exerting stronger effects than drought. Combined stress triggered the strongest responses in T. vulgaris and T. serpyllum, whereas T. kotschyanus tended to respond more to individual stressors. In contrast to species-specific metabolic responses, phytohormones exhibited treatment-specific patterns, with herbivory inducing the most pronounced changes across all measured phytohormones. Hormonal and metabolic adaptations were associated with reduced larval performance on stressed plants. Overall, the results show that the thyme species studied here respond to drought and herbivory through species-specific modulations of secondary metabolism. The integration of transcriptome, metabolome and phytohormone data provides new insights into the dynamic responses of Mediterranean aromatic plants to abiotic, biotic and combined stress factors, with implications for plant protection and resilience under climate change scenarios.